THE CONCEPT OF EARLY SEX EDUCATION IN VERSES OF QUR’AN (CONTENT ANALYSIS ON MA’ANI SCIENCE PERSPECTIVE) - Atikah, Tiara; Nurmala, Mia; Nurbayan, Yayan (JURNAL TARBIYAH, 2024)
Every year, there is no avoiding the increase in sex-related problems in Indonesia, with children being one of the victims. Therefore, this highlights the significance of early sex education. By applying the concepts of kalam khabar and kalam insya' in verses of Qur’an, this research seeks to ascertain the notion of sex education at an early age. The approach to the research methodology is a library study technique combined with a qualitative way of content analysis. The following are the findings of this study: 1) Surah An-Nur: 30 gives directions for limiting views and upholding the opposite sex's modesty.; 2) Surah An-Nur: 31 gives directions on covering the private parts and dress etiquette.; 3) Surah An-Nur: 58–59 is an order and faidhatul khabar to ask permission to enter the parents' room, especially for children who have reached puberty.; 4) Surah Al-Isra: 32 is a prohibition against committing adultery or approaching it, and as a faidhatul khabar that adultery is a very heinous act and a very bad act in channeling biological needs. These four verses form the concept of the Islamic curriculum for sex and moral education at an early age.